2001
DOI: 10.1300/j027v19n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Services Offered by Hospitals: Predicting Services by Internal and External Community Characteristics

Abstract: This article explores the role of hospitals in providing geriatric services and identifies associated community and hospital characteristics. The sample is 4571 community hospitals responding to the 1995 American Hospital Association (AHA) Annual Survey. Most hospitals offer some geriatric services; the mean is 3.3. The dependent variable is an index of 13 geriatric services created from the AHA data. Independent variables are taken from the AHA survey, Area Resource File, and census data. Regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
4
0
3
Order By: Relevance
“…Further, the same study revealed that enabling factors such as wealth status and earnings were positively associated with health services use among older adults in Uganda. Evashwick et al (1984) used the model to examine health services utilisation among older adults in the United States and found that need factors (i.e., physical health condition and perceived health status) were important predictors of physician consultations, hospitalisations, ambulatory care and home care services use, while predisposing factors (i.e., age, sex, education, marital status, race and use of preventive health services) were better predictors of dental services use.…”
Section: Theoretical Considerations For the Importance Of Access To F...mentioning
confidence: 99%
“…Further, the same study revealed that enabling factors such as wealth status and earnings were positively associated with health services use among older adults in Uganda. Evashwick et al (1984) used the model to examine health services utilisation among older adults in the United States and found that need factors (i.e., physical health condition and perceived health status) were important predictors of physician consultations, hospitalisations, ambulatory care and home care services use, while predisposing factors (i.e., age, sex, education, marital status, race and use of preventive health services) were better predictors of dental services use.…”
Section: Theoretical Considerations For the Importance Of Access To F...mentioning
confidence: 99%
“…The domains in our conceptual framework were derived from those identified in specific studies on geriatric services, 1,18,19 other literature, 21,22 and clinical experience: inpatient medical services, discharge planning services, integration with post-acute care, services to improve access to care, health maintenance and support, and organizational characteristics. We removed services that were either not targeted towards an adult population (e.g., neonatal intensive care), or were specialized technologies geared to specific needs (e.g., stereotactic radiosurgery).…”
Section: Methodsmentioning
confidence: 99%
“…In the 1980s, Evashwick and Alexander, et al described the range of services hospitals provide to older adults 1,18,19 and found that “outreach services” extending hospital programs and activities to the community identified serious commitment to robust geriatric service provision. However, prior taxonomies of services outlined in these papers may be obsolete, given the substantial changes in healthcare over the last 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited comparability to the current study, as recent studies examining readmission risk or mortality often focus on patient-level characteristics and exclude hospital-level or regional characteristics. However, the work by Alexander and Evashwick in the 1980s examined senior services, (Alexander et al, 1984;Evashwick et al, 1984;Evashwick et al, 1985) and Hartz in the 1980s and 1990s demonstrated a relationship between hospital ownership status and mortality. (Hartz et al, 1989;Kuhn et al, 1994) More recently, Sacks found an association among hospital characteristics and measures of surgical quality, (Sacks et al, 2015(Sacks et al, , 2016 and Wadhera found a general increase in mortality after implementation of the Hospital Readmissions Reduction Program.…”
Section: Interpretation Within the Context Of The Wider Literaturementioning
confidence: 99%